2014
DOI: 10.3857/roj.2014.32.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency fracture after radiation therapy

Abstract: Insufficiency fracture occurs when normal or physiological stress applied to weakened bone with demineralization and decreased elastic resistance. Recently, many studies reported the development of IF after radiation therapy (RT) in gynecological cancer, prostate cancer, anal cancer and rectal cancer. The RT-induced insufficiency fracture is a common complication during the follow-up using modern imaging studies. The clinical suspicion and knowledge the characteristic imaging patterns of insufficiency fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 37 publications
1
49
0
4
Order By: Relevance
“…Moreover, patients might undergo a biopsy or be treated by inappropriate chemotherapy or RT to their weakened bone. 2,3,10,24 It is important to note that not all pelvic IFs are due to radiation. According to many studies, the most important risk factor for pelvic IF is osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients might undergo a biopsy or be treated by inappropriate chemotherapy or RT to their weakened bone. 2,3,10,24 It is important to note that not all pelvic IFs are due to radiation. According to many studies, the most important risk factor for pelvic IF is osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes include rheumatoid arthritis, prolonged use of corticosteroids, hyperparathyroidism, and radiotherapy (RT). 2,3 Pelvic RT has been considered an essential method for the treatment of cervical cancer. Although radiation-induced IFs were considered a relatively rare adverse event after pelvic RT in patients with cervical cancer, several clinical investigations have shown that IFs are more common than previously thought.…”
mentioning
confidence: 99%
“…In addition to the possibility of inducing hypo-gonadism, radiation therapy might also directly damage bone, which results in insufficiency fractures that are common in the pelvis in gynaecological, prostate, anal and rectal cancers, and in the ribs 96 . The development of an expanding series of radiopharmaceuticals might help to alleviate some of these important limitations.…”
Section: Managing Skeletal Complications Of Cancermentioning
confidence: 99%
“…Stress fractures can also develop after radiotherapy in patients who undergo long-term treatment with corticosteroids, sodium fluoride, etidronic acid and methotrexate [7,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Zła ma nia po wol ne mo gą po wstać też u pa cjen tów po ra dio te ra pii, za ży wa ją cych prze wle kle le ki ta kie jak gli ko kor ty ko ste ro idy, flu orek so du, kwas eti dryno wy i me to trek sat [7,[12][13][14][15]. turned to work.…”
Section: Dys Ku Sjaunclassified